Juridical Review of the Confidentiality of Medical Check-Up (MCU) Results of Employees in Industrial Relations in Indonesia - Hidayat, Asep Nurman (Civiliza Publishing, 2025)
Medical Check-Up (MCU) is a legal requirement in industrial relations that serves to ensure employee health and occupational safety. However, the results of the MCU contain personal data that is sensitive and must be protected based on the provisions of medical confidentiality and laws and regulations in Indonesia. This study aims to analyze the legal framework that governs the confidentiality of MCU results, identify potential violations of the law, and provide juridical recommendations in efforts to protect employee health information. This study uses a normative juridical method with a legislative and conceptual approach. Data were obtained through literature studies that included primary, secondary, and tertiary legal materials, then analyzed descriptively and qualitatively. The results of the study show that the Health Law, the Employment Law, and the Personal Data Protection Law in Indonesia collectively form a strong legal foundation in recognizing the results of MCU as specific personal data that must be kept confidential. However, its implementation is still weak due to overlapping regulations, limited institutional capacity, and weak cybersecurity practices. Strengthening law enforcement, regulatory coordination, and institutional capacity are needed so that legal protection can be translated into real data privacy protection. Thus, the confidentiality of MCU results can only be effectively enforced through the synergy between legal certainty, professional ethics, and institutional governance.